The Relationship between the Atmospheric Heat Source over Tibetan Plateau and the Westerly-Monsoon Evolution in August and Its Physical Mechanism - Chunxue Wang; Yueqing Li (Advances in Meteorology, 2022)
In this study, the relationship between the East Asian subtropical westerly jet (EASWJ) and the East Asian summer monsoon (EASM) (westerly monsoon) and the correlation with the atmospheric heat source (AHS) on the Tibetan plateau (TP), especially the possible connection of the sudden enhancement of the correlation in August were analyzed. The results show that there is a significant correlation between the EASWJ and the EASM from June to October in terms of both intra-annual variability and interannual fluctuations, and the correlation between the AHS over TP and the EASWJ and the EASM during the same period is significantly enhanced in August. The synthetic analysis indicated that when the AHS was strong, a positive anomaly of a horizontal temperature gradient appeared over TP, which was conducive to the southward shift of the high-altitude temperature gradient center, resulting in the southward position of the axis of the 200 hPa westerly jet, and an upward and downward inclined westerly anomaly zone appeared from the south slope of TP to the main body and its north slope. Meanwhile, the East Asia–Pacific (EAP) teleconnection pattern with a negative phase appeared at 500 hPa, and TP to western Japan was located in the negative value area of the wave train. The AHS was conducive to the enhancement of the EAP negative phase, which was not conducive to the further northward transportation of water vapor by the EASM. On the contrary, when the AHS on TP was weak, the position of the westerly jet was northward and the EAP positive phase enhanced, contributing to the further northward transport of water vapor from the EASM.